English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Y=2x²-3x-2
Y=x-4

Iv already done this using a graph but im getting mixed up rearranging the formular can anybody help?

2007-12-03 23:57:50 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

2x² - 3x - 2 = x - 4
2x² - 4x + 2 = 0
x² - 2x + 1 = 0
(x - 1)(x - 1) = 0
x = 1 (twice)
y = - 3

x = 1 , y = - 3

2007-12-04 00:35:49 · answer #1 · answered by Como 7 · 2 1

Put y = x - 4 into y = 2x² - 3x - 2, getting:

y = x - 4 = 2x² - 3x - 2 or, transferring every term to one of the sides:

2x² - 3x - 2 - x + 4 = 0 --> 2x² - 4x + 2 = 0. Divide throughout by 2:

x² - 2x + 1= 0 or (x - 1)² = 0. hence x = 1. Put this value of x in either of the equations for y such as in: y = x - 4 = 1 - 4 = - 3. Finally solution is: x = 1, y = - 3.

2007-12-04 08:08:30 · answer #2 · answered by quidwai 4 · 1 1

Set them equal to each other....

2x^2 - 3x - 2 = x - 4
2x^2 + 2 = 4x

2x^2 - 4x + 2 = 0
(2x - 2) (x - 1)

x = 1 (Single solution)

2007-12-04 08:01:42 · answer #3 · answered by Doctor Q 6 · 1 0

y = 2x^2 - 3x - 2
y = x - 4

So putting both together,

2x^2 - 3x - 2 = x - 4
2x^2 - 4x + 2 = 0
x^2 - 2x + 1 = 0
(x-1)^2 = 0
x = 1

y = x - 4
y = 1 - 4
y = -3

x = 1, y = -3

2007-12-04 08:03:04 · answer #4 · answered by Tan Z 3 · 1 0

fedest.com, questions and answers